Peran Laporan Akuntansi Manajerial dalam Pengambilan Keputusan Strategis Manajemen - Fajar Damar Noviyanto; Annisa Nurul Destiana; Rezika Siti Marina; Shafara Dias Tuti; Husni Mubarok (CV. Denasya Smart Publisher, 2025)
Managerial accounting reports play a critical role in providing relevant financial and nonfinancial information for management in the strategic decision-making process. This study aims to analyze the extent to which managerial accounting reports are utilized as a basis for planning, controlling, and evaluating strategic decisions within an organization. Using a quantitative descriptive approach, data were collected through questionnaires distributed to managers from various manufacturing sector companies. The results show that the accuracy, relevance, and timeliness of managerial reports significantly influence the quality of strategic decisions made by management. These findings emphasize that the integration of managerial accounting information into the strategic process is crucial for enhancing organizational competitiveness and performance.